Effect of Parent’s International Migration on the Educational Performances of Left-Behind Children in Morocco - El Alaoui, Aicha; Ahbala, Salah (European Scientific Journal, ESJ, 2024)
This study tries to examine the effects of parent’s international migration on educational outcomes of left-behind children, focusing especially On the relative importance of family environment and school characteristics to educational achievements of left-behind children. For that, a sample from the survey study in Fkih Ben Salah as a small town in Morocco, located in the Béni Mellal-Khénifra region. This survey is administered in 2020 on 407 children from 16 primary school. The results of the prospensity score matching method showed that the internzationale migration of parents had a significant effect on the school performance of their left behind children ;furthermore ,the analysis using the Oaxaca -Blinder decomposition showed that 36.34% of the differences in the children’s school performance in first semester for year of 2020 can be explained by student–teacher ratio, size class and socio-economic index of class are 12.82%,38.47% and 31.35% of the gap, respectively. The empirical findings reveal also that Left behind children are at risk of facing social exclusion, especially in public schools.